Coagulation-related genes for thyroid cancer prognosis, immune infltration, staging, and drug sensitivity - Sun, Yuxiao; Zhang, Yifei; Yang, Yuchuan; Liu, Weihao; Yin, Detao (Frontiers in Immunology, 2024)
Introduction Thyroid cancer (THCA) is the most common endocrine tumor. Coagulation may be associated with the development of cancer, but its role in THCA patients is not yet clear. Methods In this study, we determined the predictive value of coagulation biomarker D-dimer for THCA patient lateral lymph node metastasis (LLNM) through receiver operating characteristics (ROC) analysis and logistic regression analysis. Subsequently, this study used the TCGA database to identify coagulation-related molecular subtypes through consensus clustering analysis and compared their prognosis. We identified coagulation-related genes (CRGs) associated with prognosis in thyroid cancer through gene expression data and clinical information, and constructed a prognostic model by selecting the prognostic CRGs using LASSO regression. Patients were divided into high-risk and low-risk groups based on the median score. Subsequently, prognosis, clinical characteristics, gene mutation occurrence, immune infiltration, function, and drug sensitivity of the two groups were analyzed. We also constructed a nomogram combining the model and clinical features. Finally, the expression of the prognostic CRGs was validated by RT-qPCR. Results D-dimers had better performance in predicting LLNM(the area under the curve was 0.656 (95% CI 0.580-0.733), with a cut-off value of 0.065 mg/l), and D-dimer>0.065mg/l was an independent predictor of LLNM. Then, we selected 8 prognostic CRGs to construct a predictive model. The prognosis of low-risk group patients was significantly better than that of high-risk group (P<0.001). The results showed significant differences in clinical characteristics, gene mutation occurrence, immune infiltration, function, and drug sensitivity between the high-risk and low-risk groups. We validated by qPCR that these 8 prognostic CRGs were overexpressed in THCA cell lines. Discussion Overall, this study provided an in-depth exploration of the potential role of the coagulation in thyroid cancer and its clinical significance, offering a new theoretical basis and research direction for personalized therapy and prognostic evaluation.